Nonsurgical Management of Persistent and Hemodynamically Significant Patent Ductus Arteriosus among Extremely Low Birth Weight Infants: A Propensity Score Matched Analysis - Bhat, Ramachandra; Dolma, Kalsang; Zayek, Michael; Batten, Lynn; Peevy, Keith; Eyal, Fabien (American Journal of Perinatology, 2018)
Objective The objective of this study was to evaluate the impact of a nonsurgical approach (with the incorporation of late postnatal hydrocortisone treatment to facilitate extubation) in comparison to the surgical approach for the management of persistent hemodynamically significant patent ductus arteriosus (hsPDA) among chronically ventilator-dependent extremely low birth weight (ELBW) infants.Methods In this retrospective study, ELBW infants with a diagnosis of hsPDA (diagnosed based on the echocardiographic criteria and chronic ventilator dependence) that were persistent beyond 14 days of postnatal age despite adequate medical treatment were included.Results Out of 127 infants (surgical approach group, n = 67 and nonsurgical approach group, n = 60), 72 infants were matched based on the propensity scores. In the matched cohort, in comparison to infants managed with the surgical approach (control group, n = 36), infants in the nonsurgical approach group (treatment group, n = 36) had a lower rate of surgical ligation (14 vs. 100%, p = < 0.001), but there were no differences in both primary outcome (death or bronchopulmonary dysplasia) and secondary outcome measures.Conclusion For chronically ventilator-dependent ELBW infants with persistent hsPDA, a nonsurgical management approach is associated with a reduced rate of surgical ligation of PDA, but not associated with increased risk of adverse major short-term neonatal outcomes.
Keywords: patent ductus arteriosus; extremely low birth weight infants; mechanical ventilation; bronchopulmonary dysplasia; hydrocortisone